KONEKSI POLITIK MEMODERASI PENGARUH FINANCIAL DISTRESS DAN INTENSITAS MODAL TERHADAP PENGHINDARAN PAJAK - Achmad Sofian (2023)
This research is a quantitative study that aims to determine the role of political connections in moderating the effect of financial distress and capital intensity on tax evasion. This study uses secondary data with a population of mining companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period. The observational data of this study amounted to 96 data from 32 sample companies selected through the purposive sampling method and predetermined criteria. The research hypothesis was tested using multiple linear regression analysis and Moderated Regression Analysis (MRA) using STATA version 16 with a significance value of 5%. The results of testing the hypothesis show that (1) financial distress has a positive effect on tax avoidance, (2) capital intensity has no effect on tax avoidance, (3) political connections cannot moderate the effect of financial distress on tax avoidance, (4) political connections do not can moderate the effect of capital intensity on tax avoidance.